2015
DOI: 10.1103/physrevb.92.014508
|View full text |Cite
|
Sign up to set email alerts
|

Zero-energy peak and triplet correlations in nanoscale superconductor/ferromagnet/ferromagnet spin valves

Abstract: Using a self-consistent Bogoliubov-de Gennes approach, we theoretically study the proximity-induced density of states (DOS) in clean SF F spin-valves with noncollinear exchange fields. Our results clearly demonstrate a direct correlation between the presence of a zero energy peak (ZEP) in the DOS spectrum and the persistence of spin-1 triplet pair correlations. By systematically varying the geometrical and material parameters governing the spin-valve, we point out to experimentally optimal system configuration… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 60 publications
2
53
0
Order By: Relevance
“…Although OTE s-wave pairing has been discussed in diffusive ferromagnet (DF)/conventional spin-singlet swave superconductor junctions, it is difficult to realize pure OTE s-wave pairing state in a DF [60][61][62][63][64][65][66][67][68][69][70][71]. Conversely, the demonstrated anomalous proximity effect generated by ZESABSs specific to unconventional superconductors is remarkable, as it can induce a purely odd-frequency pairing or at least a significant amount of it at low energy.…”
Section: Introductionmentioning
confidence: 99%
“…Although OTE s-wave pairing has been discussed in diffusive ferromagnet (DF)/conventional spin-singlet swave superconductor junctions, it is difficult to realize pure OTE s-wave pairing state in a DF [60][61][62][63][64][65][66][67][68][69][70][71]. Conversely, the demonstrated anomalous proximity effect generated by ZESABSs specific to unconventional superconductors is remarkable, as it can induce a purely odd-frequency pairing or at least a significant amount of it at low energy.…”
Section: Introductionmentioning
confidence: 99%
“…If differing ferromagnetic materials, constituting the left and right F layers are chosen properly, they respond to an external magnetic field in different ways, providing active control of the magnetization misalignment angles through variations in the intensity and direction of an external magnetic field. It was shown that the superconducting transition temperature [46][47][48][49][50] and density of states 13,[51][52][53][54] reveal prominent signatures of the long-ranged spin-triplet superconductivity 5 as a function of magnetization misalignment. Nevertheless, a direct and clear observation of the equal-spin triplet pairings in superconducting hybrids is still elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly zero energy states (ZES) are not necessarily MBS. For example, Andreev bounds states can also occur at zero energy [13,[27][28][29][62][63][64][65][66][67]. Here ZES denote any states with (nearly) zero energy, being MBS or not and are related to the well-known zero bias conductance peak [11,12].…”
mentioning
confidence: 99%